Mengukur Kinerja Perusahaan: Kajian tentang Profitabilitas, Leverage, Nilai Perusahaan, dan Return Saham pada Perusahaan Property dan Real Estate yang Terdaftar di BEI - Yunita, Nurul; Hermuningsih, Sri; Maulida, Alfiatul (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
The study aims to examine the effect of profitability and leverage on firm value and stock returns. In addition, the study also analyzes how firm value mediates the effect of profitability and leverage on stock returns in the property and real estate sector listed on the IDX for the 2019–2023 period. The sample was selected using a purposive sampling technique, resulting in 18 companies with complete financial reports. Multiple linear regression analysis was used to test the direct effect, while the Sobel test analyzed the mediation effect. Data processing was carried out using SPSS. The results reveal that profitability has a significant effect on firm value and stock returns, while leverage does not show a significant effect on either firm value or stock returns. Firm value is proven to have a positive and significant effect on stock returns.